Supporting the Paternal Role and Transition Home From the NICU: A Mixed Method Study - Bryana Salazar (Scholarworks @ WMU, 2022)
Background: Limited research has focused solely on fathers' experiences following a Neonatal Intensive Care Unit (NICU) stay. The study aimed to identify occupational therapy's role in supporting paternal wellness and mental health through routines and occupations following discharge. Methods: Online surveys (n = 32) and virtual interviews (n = 11) were collected to complete a mixed method design study. Interviews were manually transcribed and coded to perform thematic analysis. Results: Five themes were identified: adjusting expectations, changes in priorities, the unexpected toll of the NICU, coping and healing, and fathers and health care providers. This study emphasized how the continued difficulties and emotional toll following a NICU stay affects fathers' engagement in self-care because of feelings of guilt. Narrative writing became an important occupation for fathers by creating a therapeutic and community space for them to cope. Furthermore, this study indicates areas in which to improve communication between fathers and health care providers. Conclusions: These findings indicate that fathers would benefit from continued support post NICU discharge because of the continued challenges following a NICU stay. Occupational therapists can help support NICU fathers' occupational balance to promote positive engagement in self-care activities, and these needs can be addressed during interactions in early intervention.